Penerapan Metode Bermain Peran dalam Peningkatan Kepercayaan Diri Siswa Kelas IV SD Inpres 5 Taipa Laga - Sry Iramaya S. Mangge; Yusdin Bin Mahmudin Gagaramusu; Zulnuraini Zulnuraini; Dyah Rahmawati (JURNAL DIKDAS, 2025)
Based on the research and data analysis, it was found that the application of the role-playing method can improve students' self-confidence. This was known because before the action, the level of self-confidence of students only reached 50%. After the first cycle of action, the average percentage of students' self-confidence increased by 57.35%. Then, in the second cycle, it increased again to 75%. The results of student activity observations in the first cycle obtained a percentage of 64.44% and in the second cycle obtained 71.11%. Meanwhile, the results of student activity observations in the second cycle, the first meeting obtained a percentage of 77.77% and the second meeting obtained 88.88%. The results of teacher activity observations in the first cycle, the first meeting obtained 71.11% and the second meeting obtained 77.77%, while in the second cycle, the first meeting obtained 82.22% and the second meeting obtained 91.11%. Based on these results, it can be concluded that the application of the role-playing method can improve the self-confidence of Class IV B students at SD Inpres 5 Taipa Laga.